EVALUASI STRATEGI PADA PT. BANK SYARIAH BUKOPIN - , Kiki Firman; , Dr. Agus Setiawan, M.Soc.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Development of Syariah Bank in Indonesia is more rapid currently. This begins with the enforcement of act No.21 Year 2008 on Syariah Banking Issued on 16 th July 2008 that the development of national syariah banking industry has adequate legal ground and will stimulate its growth more rapidly. PT. Bank Syariah Bukopin is the fifth Bank in Indonesia until 2009 Bukopin Syariah Bank has booked a profit in the amount of Rp. 2,7 billion, total asset of Rp. 1,9 trillion, the fund acquired from the third party in the amount of Rp. 1,3 trillion, and the distributed financing in the amount of Rp. 1,3 trillion. The basic problem faced at present is how in the next years Bukopin Syariah Bank can keep growing property, with the key to evaluate the strategy periodically? In order to know about the answer, it is necessary to analyze previously the external environment, consisting of five forces, driving forces, key success factor, SWOT and general strategy. Furthermore,internal environment of the company should be analyzed in terms of financial aspect, human resources aspect, and marketing aspect. The external analysis indicates that syariah banking highly depends on the preparation of strategy because the supporting factors have great influence to the industry so as to change the structure of industry as a whole because it will support the suitability of the company strategy to the existing condition. From the internal analysis, Bukopin Syariah Bank has to keep optimizing the capability for achievement of the company goal.